2018
DOI: 10.1063/1.5018629
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stimulated Raman scattering by femtosecond ultraviolet plasma grating in water

Abstract: Efficient forward stimulated Raman scattering (SRS) was observed along 400-nm femtosecond (fs) laser filaments in water. SRS conversion dominated over self-phase modulation induced continuum generation as the input pulse energy was above 4 μJ (∼30 Pcr), implying that plasma in the aqueous filamentation channel played an important role in compensating for the group velocity walk-off between the pump and Stokes pulses. By overlapping two synchronous fs 400-nm filaments to form plasma grating in water, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Of great interest are works devoted to the study of stimulated Raman scattering (SRS) spectra of light [ 27–29 ] and heavy [ 29,30 ] water, as well as their mixtures. [ 31–33 ] It is known that SRS lasing in a liquid volume of water occurs with the formation of plasma as a result of optical breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…Of great interest are works devoted to the study of stimulated Raman scattering (SRS) spectra of light [ 27–29 ] and heavy [ 29,30 ] water, as well as their mixtures. [ 31–33 ] It is known that SRS lasing in a liquid volume of water occurs with the formation of plasma as a result of optical breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the initial optical process, there are some other complex phenomena including self‐focusing, laser‐induced breakdown, shock wave generation, and cavity bubble . Therefore, SRS is widely used to study the properties of liquid water, for example, Liu et al found the enhancement of SRS conversion along ultraviolet femtosecond laser filaments in water; Yuan et al studied the effect of divergence, polarizations, and pulse shapes on the SRS of liquid water by 532‐nm laser; Kumar et al compared SRS spectra of water by the 355‐, 532‐, and 1,064‐nm lasers . Our group has also studied the structures of liquid water molecules under different conditions by SRS, but the details of two‐state model of water are not clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…h) Utilization of Au nanoparticles as contrast agents for imaging filamentary plasma grating in experiments of enhanced stimulated Raman scattering through a water sample. Reproduced with permission [171]. Copyright 2018, American Institute of Physics.…”
mentioning
confidence: 99%